2014
DOI: 10.1371/journal.pone.0083217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Mild Cognitive Impairment in Xi’an: A Community-Based Study among the Elders

Abstract: Mild cognitive impairment (MCI) is an intermediate stage between normal cognitive function and dementia among aging individuals. This study was designed to estimate the prevalence of MCI and explore the possible risk factors including gender disparities among community-dwelling older individuals. The study was conducted in Xi’an, China. This is a cross-sectional study. A total of 815 individuals, 60 years and older were selected by stratified random cluster sampling. Cognitive function was measured using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…Our study observed that subjects who achieved secondary and tertiary education had lower risk of cognitive impairment. This finding is consistent with a number of other studies which showed that people with primary school education had higher risk to develop cognitive impairment 18,19 . This implies that every country should take appropriate measures to prevent school drop-outs and promote higher education by providing free education at least up to secondary level.…”
Section: Based On the Logistic Regression Shown Insupporting
confidence: 92%
See 1 more Smart Citation
“…Our study observed that subjects who achieved secondary and tertiary education had lower risk of cognitive impairment. This finding is consistent with a number of other studies which showed that people with primary school education had higher risk to develop cognitive impairment 18,19 . This implies that every country should take appropriate measures to prevent school drop-outs and promote higher education by providing free education at least up to secondary level.…”
Section: Based On the Logistic Regression Shown Insupporting
confidence: 92%
“…Studies have reported that moderate alcohol intake have protective effect on cognitive function 19,22,25 . However, the percentage of subjects who consumed alcohol in our study was minimal (7.4%), so no conclusion could be drawn.…”
Section: Based On the Logistic Regression Shown Inmentioning
confidence: 99%
“…[11][12][13] The wide variation in the prevalence of cognitive impairment could be due to differences in diagnostic criteria, rating instruments, or sampling methods. For example, some studies established the diagnosis of cognitive impairment with the Mini-Mental State Examination, 12,14,35,36 whereas others used the Clinical Dementia Rating scale. 37 In addition, different age ranges may also influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been shown to be sensitive in the detection of dementia within the Chinese population (Su et al . ).…”
Section: Methodsmentioning
confidence: 97%